Vantagem competitiva no mercado brasileiro de telecomunicações: uma análise fundamentada na visão baseada em recursos no período pós-privatização - Ribeiro, Rodolfo (2010)
This dissertation aims to assess the evolution of Brazilian telecommunications market s main indexes after its privatization and to verify the resources responsible for superior performance of some competitors, between the years of 1999 and 2008. Built on Resource Based View (RBV), this research used Data Envelopment Analysis (DEA) to rank organizational performance, in a model which output was Return on Assets (ROA). With organizational efficiency scores generated by DEA model, a regression was applied to investigate which resources are relevant for company performance. Organizational attributes like market share (telephone lines and revenue generator units), product portfolio and capital origin were significant to determine organizational performance. This results suggests that network effects and a strategy based on a convergent portfolio diversification are significant factors for company performance. One of the intangible factors assessed, registered trademarks, didn t have significance on performance. Companies controlled by national groups presented better results, suggesting that part of performance achieved could be associated with previous knowledge about the country of operation